Cloning and expression analysis of PRL and PRLR genes in black Muscovy duck. Issue 1 (2nd January 2020) - Li, X.; Ji, W.; Sun, G.; Xiao, W.; Bian, Y.; Qing, H.
ABSTRACT: 1. Prolactin hormone (governed by the PRL gene) is secreted by the anterior pituitary of animals, which combines with its receptor (prolactin receptor, PRLR ) to act on target cells. Both PRL and PRLR are mainly associated with reproductive performance. The genetic mechanism of nesting in poultry is not yet clear, and so the aim of the current study was to determine expression patterns of PRL and PRLR at different times across the breeding stages of black Muscovy ducks. 2. In this study, the CDS regions of PRL and PRLR were determined by RACE sequencing. The expression levels of PRL and PRLR in the pituitary, ovary and uterus from the black Muscovy duck were compared and analysed during the pre-laying, laying and nesting periods. 3. The results showed that PRL and PRLR are highly homologous in a variety of poultry species. The expression of the PRL gene in the pituitary was the highest, which was significantly higher than seen in the ovary and uterus. This trend ran through the entire prenatal period, i.e. the laying period and the nesting period. The expression level of the PRLR gene in the pituitary and ovary was generally low, and expression in the uterus was the highest. There was no significant difference in expression of the PRLR gene between pituitary and ovary during different periods, but the expression level of the PRLR gene in the uterus reached its highest level during the nesting stage, which was significantly higher than seen in the early laying period.